The Correlation Between the Palestinian Civil Society Institutions and the Universities (Status: The Palestine Technical University Kadourie with Tulkarm Institutions) - Sweis, Khalid Mohammed (Journal of Social Economics Research, 2015)
The study aimed to determine the effect of the correlation between the universities and institutions of the Palestinian civil society, it discuss’ and analyzes the academic community which are about (120) non-profit association. However, questionnaires were distributed on only (95) of these non- profit organizations, and (80) questionnaire were given back, and so, samples were taken in a comprehensive destination style, and were used in the analysis of packets Statistical Social Sciences (SPSS) program and had the following processors: frequencies, percentages, averages, test T for the independent samples, and the contrast unilateral analysis, the equation Cronbach’s alpha to extract the reliability coefficient, however, the results show that it is necessary to prepare human resources scientifically, technically and administratively in relation to work reality, as well as, the participation of the Universities in the community initiatives, and the creation of twinning between universities and local facilities.The study also recommended the need to provide free or reduce educational fees for humanitarian associations and suggests universities to adopt physical funding for the ideas of students in community of work and to increase the financial aids for the ads through the official university sites activities with local institutions and also to work on the development of economic and social development plans participating universities and facilities local.